Principles of anatomy & physiology : Organization, support and movement and control systems of the human body - Tortora, Gerard J.; Tortora, Gerard J.; Derrickson, Bryan (New Jersesy, John Wiley, 2011)
The thirteenth edition of the phenomenally successful Principles of Anatomy and Physiology continues to set the standard for the discipline. The authors maintained a superb balance between structure and function and continue to emphasize the correlations between normal physiology and pathophysiology, normal anatomy and pathology, and homeostasis and homeostatic imbalances. The acclaimed illustration program continues to be refined and is unsurpassed in the market. The thirteenth edition is fully integrated with a host of innovative electronic media, including WileyPlus 5.0 (access purchased separately.) No other text and package offers a teaching and learning environment as rich and complete.
Glossary G1-G29p.; Index I1-I32p.
Keywords: Anatomy; Biology; Physiology; Environmental Biology